Gender difference in overconfidence and household financial literacy - Lawrence, Edward R.; Nguyen, Thanh D.; Wick, Benedikt (Journal of Banking & Finance, 2024)
We study overconfidence related to financial knowledge among men and women within U.S. households, venturing beyond prior research confined to subsamples such as CEOs, retail investors, and older adults. By expanding our study to the broader U.S. population, we provide evidence that women, on average, exhibit greater overconfidence than men – a discrepancy attributable to the gender difference in financial knowledge. We find a positive association between overconfidence and both investment risk-taking and savings behavior, while it correlates inversely with prudent credit card management. Our findings emphasize the instrumental role of financial literacy in mitigating overconfidence, providing a deeper understanding of the interaction between gender, overconfidence, and financial literacy. Our results carry profound implications for policy interventions and educational strategies.